The nudibranch Berghia stephanieae (Valdés, 2005) is not able to initiate a functional symbiosome-like environment to maintain Breviolum minutum (J.E.Parkinson & LaJeunesse 2018) - Clavijo, Jenny Melo; Sickinger, Corinna; Bleidißel, Sabrina; Gasparoni, Gilles; Tierling, Sascha; Preisfeld, Angelika; Christa, Gregor (Frontiers in Marine Science, 2022)
Photosymbiosis is found in different animal lineages and is best understood in cnidarians. A successful initiation and maintenance of the symbiosis between the animal hosts and the photosymbiotic partners is based on a recognition by specific host receptors. This triggers signaling cascades that promote the photobiont tolerance by the host, including an interpartner nutrient exchange and the ability of the host to cope with increased levels of reactive oxygen species (ROS) generated by the photobiont. Key to the successful symbiosis is the inhibition of the phagosomal maturation resulting in the formation of the symbiosome. In animals other than cnidarians, little is known about the photosymbiosis initiation and maintenance, for instance in sea slugs belonging to the Nudibranchia. Here, we investigated the gene expression profile of Berghia stephanieae, which is able to incorporate Breviolum minutum from its cnidarian prey Exaiptasia diaphana (Rapp, 1829) but is not able to maintain the algae for more than a couple of days during starvation. We show that the recognition of the algae is based on similar mechanisms present in cnidarians, and identified some additional candidate genes that might be molluscan specific for photobiont recognition. Downstream, B. stephanieae responds to increased levels of ROS but is not able to stop the phagosomal maturation nor decrease the immune response against B. minutum, which seem to be the key factors missing in B. stephanieae that accounts for the unstable symbiosis in this slug. Hence, B. stephanieae can be considered a transitional state towards a stable photosymbiosis and can help to elucidate general aspects of the evolutionary processes involved in establishing photosymbioses in animals.